(untitled) (Ius Novum, 2022)
Due to the amendment, which entered into force on January 1, 2022, a number of provisions in Chapter XI of Misdemeanour Code concerning safety and order in communication were significantly changed. The legislator decided to introduce new types of prohibited acts and significantly increased the amount of the fine for certain offenses. These changes are revolutionary, which is also associated with controversy. This is because some of the changes made raise doubts due to the higher degree of their repression, which makes the punishability of certain offenses disproportionate in relation to similar crimes under the Penal Code. This issue will be presented later in the article.